13m-27=9m-6

Simple and best practice solution for 13m-27=9m-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13m-27=9m-6 equation:


Simplifying
13m + -27 = 9m + -6

Reorder the terms:
-27 + 13m = 9m + -6

Reorder the terms:
-27 + 13m = -6 + 9m

Solving
-27 + 13m = -6 + 9m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-9m' to each side of the equation.
-27 + 13m + -9m = -6 + 9m + -9m

Combine like terms: 13m + -9m = 4m
-27 + 4m = -6 + 9m + -9m

Combine like terms: 9m + -9m = 0
-27 + 4m = -6 + 0
-27 + 4m = -6

Add '27' to each side of the equation.
-27 + 27 + 4m = -6 + 27

Combine like terms: -27 + 27 = 0
0 + 4m = -6 + 27
4m = -6 + 27

Combine like terms: -6 + 27 = 21
4m = 21

Divide each side by '4'.
m = 5.25

Simplifying
m = 5.25

See similar equations:

| -4x-20= | | I=0.4/5 | | 24=X-24 | | (14-2x)(8-2x)=40 | | (x^2)+2t-5=19 | | 7(6y-5(4y-11))=7-8y | | (8x+7)(8x+7)(4x+3)(x+1)=15 | | 3(15x)+7y=208 | | -X-17=3x-1 | | 0.5(6k-0.5)-0.5(3k-0.25)-0.8(5k-2)=0 | | 3(15x)+7x=208 | | -3x-5x-1=0 | | (5ab)(-1/3a)(9b^2) | | Ln(x+2)+5=7 | | sin(6)-sin(42)-sin(66)+sin(78)=-0.5 | | sin(6)-sin(42)-sin(66)+sin(78)=0 | | 0.16=W/5 | | y=4x^3-3x^2+x^6 | | cos(5x)+cos(3x)=cos(x) | | 3logX=9 | | 5-5n=10 | | 6*5/9 | | I=w/V | | 7(4)-7=21 | | I=0.8/5 | | (10x-14)=(5x+56) | | 14(-8x-15)=-1218 | | 10x^2-25x/12=5 | | 0.20=W/5 | | 2x/3-7=2 | | 2x(6-2)=16 | | -4x(3x-5y^2+2)= |

Equations solver categories